2007
DOI: 10.1097/01.naq.0000278937.49491.34
|View full text |Cite
|
Sign up to set email alerts
|

Using Nurse Leader Development to Improve Nurse Retention and Patient Outcomes

Abstract: With many factors converging, it is critical that nurse leaders have the knowledge and competency to develop outstanding relationships with registered nurses in order to retain them and thus improve patient outcomes. Senior nurse leaders of Methodist Le Bonheur Healthcare, a 7-hospital system based in Memphis is addressing these issues through a comprehensive leader development framework. Through organizational commitment and supported by a federal grant, a program that focuses on creation of individual develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 3 publications
0
14
1
Order By: Relevance
“…A substantive body of research evidence supports the relationship between leadership and nursing retention (Taunton et al 1997, Boyle et al 1999, Alspach 2007, Herrin & Spears 2007. Therefore, it is important for senior nursing leaders to take steps to address management related issues in critical care areas.…”
Section: Discussionmentioning
confidence: 95%
“…A substantive body of research evidence supports the relationship between leadership and nursing retention (Taunton et al 1997, Boyle et al 1999, Alspach 2007, Herrin & Spears 2007. Therefore, it is important for senior nursing leaders to take steps to address management related issues in critical care areas.…”
Section: Discussionmentioning
confidence: 95%
“…As suggested by Herrin and Spears (), a supportive environment is one of the most important factors associated with job satisfaction for nurses. In addition, Lake and Friese () found nurse practice environments to have poor ratings based on nurse manager supportiveness and staffing adequacy.…”
Section: Discussionmentioning
confidence: 96%
“…Lake and Friese () found that few hospitals have practice environments that are favorable for nurses. As suggested by research, a supportive environment is one of the most important factors associated with job satisfaction for nurses, and nurse practice environments are rated poorly on nurse manager supportiveness and staffing adequacy (Herrin & Spears, ; Shirey et al., ). And yet, expressions of respect and recognition by the manager for the knowledge and contribution to the healthcare process are more important than financial rewards for professional nurses (McGuire et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important for individuals who take on nurse manager roles to be adequately prepared for these roles; for example, many Master of Nursing programmes now offer administrative foci. Ongoing professional development opportunities and support for nurses who take on these roles also need to be developed (Herrin & Spears 2007). In particular, it is critically important for nurse managers to realize their role in promoting positive perceptions of the organization.…”
Section: Discussionmentioning
confidence: 99%